PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA PEMBELAJARAN IPS DI SDN NGADIREJO KOTA KEDIRI - Wiguna, Frans Aditia; Damayanti, Susi (Universitas Nusantara PGRI Kediri, 2018)
The purpose of the research is to know whether the problem-based learning model has an effect on the students' creative thinking ability in the social studies learning material of economic activity. To achieve this objective, the researcher used experimental technique using pretest-posttest control group design design using treatment model based on problem-based learning. Furthermore, the data will be analyzed by t-test comparative analysis. Based on data analysis, it can be concluded that there is a positive effect of problem-based learning model on students' creative thinking ability. The existence of significant difference to students' creative thinking ability between using problem-based learning model and conventional learning model is proven in the acquisition table Mean 79.66 (experimental group)> 70,31 (control group) and test test result of 5,564 based on df 68 t calculate at 5% significance level of 2.00 hence the position of t-test 5,564> t-table 2,00 (α = 0,05). It can be concluded that the probability of error in this study is still below 0.05 with the high t-count price of 5,564 has a significance level of 0.000 which apparently its position is still far below the value α = 0.05. Thus this research succeeded in rejecting H0 at a significance level of 5%. Furthermore it can be concluded that H1 is proven true. It is concluded that the problem-based learning model has a positive effect on the ability of creative thinking on the social studies learning of grade five students of Ngadirejo State Elementary School in Kediri. Keywords: Problem-based learning, creative thinking.